NO ENGLISH TITLE AVAILABLE - JAUME, MIGUEL L (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1967)
Intradermal tests using formalinized saline suspensions of Brucella abortus and B melitensis were made on normal persons and those with proved brucellosis Doses of 10,000, 100,000 and 1,000,000 bacteria were used and the intensity of reaction with each
REV SOC MALACOL CARLOS DE LA TORRE
Keywords: ENGLISH, TITLE, AVAILABLE; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA CLINICA